Dinâmicas urbanas em cidades médias: a expansão de Lavras/MG (2007-2021). - Silva, Rondinely Fernando Resende Da (2023)
Medium-sized cities have been playing an important role in the socioeconomic configuration of the country, and the dynamics of space structuring are intrinsically involved with the patterns of differentiation and social separation. In this dissertation, the city of Lavras/MG is analyzed through the relationship between spatial and temporal scales, where the process of urban expansion through the dynamics and performance of real estate agents can be evidenced. The main objective of this research was to understand the geohistorical process of urban expansion in the municipality of Lavras and for the construction of the analysis, the processes of this dynamic were considered and described in two phases: the formation and consolidation of the municipality from the 18th century onwards and the urban expansion between the years 2007 and 2021. Considering the investigation of the trajectory of the urban expansion process of the average city of Lavras, descriptive research was chosen, with a qualitative approach, called bibliographical and documental and of a nature exploratory and interpretive. From the identification and analysis of important real estate agents that play a structuring role in the city, it was possible to understand how the actions of these agents and the role that public power assumes over urban land directly interfere in the processes of structuring and restructuring the city.